Budd–Chiari Syndrome Management: Controversies and Open Issues - Andrea Mancuso (Diagnostics, 2022)
Budd–Chiari Syndrome (BCS) is due to thrombosis of hepatic veins (HVs), inferior vena cava (IVC) or both, leading to impaired hepatic venous outflow [...]